A case study focusing on investigating the tribological performance of Cu-Sn sintered brake pad of off-high road vehicles. (November 2020) - Kumar, V Vineeth; Kumaran, S Senthil; Dhanalakshmi, S
Copper-based sintered friction materials are most suitable for heavy-duty off-road vehicles, trains, aircraft, and military applications. This present study aims to investigate the tribological performance, dominating wear mechanism of an existing copper-tin sintered friction material that is being used in armoured fighting vehicle. The brake pad was tested as per IS 2742 using the chase test machine. Especially fade cycle was carried out till 441℃ to analyze the frictional response of the material. Physical, mechanical, and tribological properties were evaluated as per industrial standards. Morphological analysis was carried out using field emission scanning electron microscopy, and wear debris analysis was carried out using scanning electron microscopy–energy dispersive X-ray analysis and X-ray diffraction analysis. The dominating wear mechanisms were found to be delamination and abrasive wear. The investigated results showed a less wear rate of 0.05 cm 3 /MJ. However, results seem to be better for high-energy applications by exhibiting excellent mechanical properties.